2021
DOI: 10.1007/s42058-021-00070-6
|View full text |Cite
|
Sign up to set email alerts
|

Digital radiograph rejection analysis during “Coronavirus disease 2019 (COVID-19) pandemic” in a tertiary care public sector hospital in Khyber Pakhtunkhwa Province of Pakistan

Abstract: Background Evaluation of X-ray reject analysis is an important quality parameter in diagnostic facility. The aim of this study was to find out the radiograph rejection and its causes during the coronavirus disease 2019 (COVID-19) pandemics as there was fear of coronavirus disease infection among the technical staff from the incoming patients in a busy, high volume public sector tertiary care hospital. Materials and method This descriptive study was conducted at Radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Firstly, the data were collected during a period that included lockdown restrictions due to the COVID‐19 pandemic, which may have impacted the normal workflow of the radiology departments. It is possible that the lockdown periods due to the COVID‐19 pandemic may have influenced the duration of examinations and the technique used by the MITs, which could have impacted the rate of positioning errors 24,25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the data were collected during a period that included lockdown restrictions due to the COVID‐19 pandemic, which may have impacted the normal workflow of the radiology departments. It is possible that the lockdown periods due to the COVID‐19 pandemic may have influenced the duration of examinations and the technique used by the MITs, which could have impacted the rate of positioning errors 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the lockdown periods due to the COVID‐19 pandemic may have influenced the duration of examinations and the technique used by the MITs, which could have impacted the rate of positioning errors. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have reported on the reject rate for radiographs [12][13][14][15][16][17][18][19][20][21]. Reject rate refers to suboptimal radiographs that are rejected or discarded, and often require repeat radiographs to obtain a diagnostic quality radiograph.…”
Section: Suboptimal Cxrs: the Problemmentioning
confidence: 99%
“…Reject rate refers to suboptimal radiographs that are rejected or discarded, and often require repeat radiographs to obtain a diagnostic quality radiograph. For CXRs, prior research reported the reject rates varying between 4% and 15% (Table 2) [14][15][16][17][18][19][20][21]. Jabbari et al evaluated 5695 radiographs in Iran and reported an 11% repeat or reject rate.…”
Section: Suboptimal Cxrs: the Problemmentioning
confidence: 99%